(untitled) (Eurasian Journal of Learning and Academic Teaching, 2023)
This article examines the role of folk traditions in education and their impact on the development of students’ personality. The advantages of including folk traditions in the educational process, including the preservation of cultural heritage, the development of creative thinking and the formation of values and social skills, are discussed. The conclusion emphasizes the need to include folk traditions in educational programs to ensure the full development of students’ personality and the preservation of cultural diversity